2013
DOI: 10.1002/adma.201302223
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Graphene/Metal Oxide Nanoparticle Hybrids for High‐Performance Capacitive Deionization of Saline Water

Abstract: A novel and general method is proposed to construct three-dimensional graphene/metal oxide nanoparticle hybrids. For the first time, it is demonstrated that this graphene-based composite with open pore structures can be used as the high-performance capacitive deionization (CDI) electrode materials, which outperform currently reported materials. This work will offer a promising way to develop highly effective CDI electrode materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
260
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 517 publications
(265 citation statements)
references
References 67 publications
(99 reference statements)
4
260
1
Order By: Relevance
“…On the other hand, among the carbonaceous materials, graphene nanosheet (GNS) has recently gained a substantial amount of attention owing to its good electrical conductivity, high theoretical specific surface area (SSA; 2630 m 2 g −1 per single layer), and excellent chemical stability and mechanical flexibility [27][28][29]. However, GNS tends to aggregate and restack together due to the van der Waals interaction among graphene layers, resulting in severe decrease of the electrochemically active surface area and the access of electrolyte ions to the surface of graphene sheets.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, among the carbonaceous materials, graphene nanosheet (GNS) has recently gained a substantial amount of attention owing to its good electrical conductivity, high theoretical specific surface area (SSA; 2630 m 2 g −1 per single layer), and excellent chemical stability and mechanical flexibility [27][28][29]. However, GNS tends to aggregate and restack together due to the van der Waals interaction among graphene layers, resulting in severe decrease of the electrochemically active surface area and the access of electrolyte ions to the surface of graphene sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Among the commonly utilized metal oxides, TiO 2 has the advantages of low cost, good chemical inertia, being eco-friendly, and ease of anchoring into the carbon structure; moreover it enhances the adsorption capacity in a CDI system [30][31][32][33]. Recently, a three-dimensional graphene/TiO 2 NP composite was proposed as an electrode for CDI [34]. In that study, the results indicated that the metal oxide NPs can beneficially inhibit the aggregation and demonstrate significant improvement in electrosorption capacity under cell only relatively high potential (1.2 V) [34].…”
Section: Introductionmentioning
confidence: 99%
“…These pioneering works hold the promise that the sluggish kinetics of HER might be circumvented if rational fabrication of the hybrid materials could be accomplished and the synergetic interactions between noble metal and metal hydroxide are exploited. However, unlike many reports on successful deposition of noble metal nanoparticles (NPs) on 2D graphene oxide (GO) sheets [24][25][26][27] , controllable growth of noble metal NPs on the layered metal hydroxide sheets is rarely realized. The difficulty lies in the fact that, with respect to the GO sheets, much fewer surface functional groups (like carboxylic acid and carbonyl) result in the reduced adsorption of noble metal ions onto the metal hydroxide sheets, making it unfavourable for heterogeneous nucleation and growth of noble metal NPs on the surface of the layered metal hydroxides.…”
mentioning
confidence: 99%